2013
DOI: 10.1111/joop.12028
|View full text |Cite
|
Sign up to set email alerts
|

Leader–member exchange, organizational identification, and job satisfaction: A social identity perspective

Abstract: This study examines the influence of leader–member exchange (LMX) on employee organizational identification and job satisfaction. Drawing upon the current literature of social identity theory, we propose a moderated mediation model with organizational identification as the mediator of the relationship between LMX and job satisfaction, and with job security as the moderator on such positive indirect link between LMX, organizational identification, and job satisfaction. We tested our hypotheses using a two‐phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
164
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(193 citation statements)
references
References 114 publications
14
164
0
1
Order By: Relevance
“…Both LMX and OID have been extensively investigated, but little has been known about the relationship between the two. A recent study found that the quality of leader-follower relationship is crucial to reinforce employee's identification to the organization, and called for more studies to robust the linkage between them [10]. Our study not only supports the linkage between LMX and OID, but also complements and extends their work by showing that WFE is an important mediation mechanism through which LMX influences OID.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Both LMX and OID have been extensively investigated, but little has been known about the relationship between the two. A recent study found that the quality of leader-follower relationship is crucial to reinforce employee's identification to the organization, and called for more studies to robust the linkage between them [10]. Our study not only supports the linkage between LMX and OID, but also complements and extends their work by showing that WFE is an important mediation mechanism through which LMX influences OID.…”
Section: Discussionsupporting
confidence: 84%
“…Given that supervisor-subordinate relationship is the basic work unit within the organization and employees often view their supervisors as agents of the organization, the quality of LMX is crucial for employees' identification to their working organization [10]. Employees with high-quality LMX will be assigned important duties and responsibilities, and have better career development within the organization.…”
Section: Lmx and Oid: Wfe As A Mediatormentioning
confidence: 99%
“…In the process of social exchange, the perception of oneness with or belongingness in an organization (i.e., OI) (Loi et al, 2014) and the psychological bond of the employee with the organization (i.e., OC) (Joo 2010;Porter et al, 1974) are enhanced. Therefore, we propose the following hypotheses:…”
Section: Lmxmentioning
confidence: 99%
“…This means then that some leader-follower dyads will be characterised by high-quality exchanges (e.g., mutual liking, trust, and respect) whereas these aspects will be neglected (or simply do not exist) in low-quality exchanges (Loi, Chan & Lam, 2014;Loi, Mao & Ngo, 2009). One implication of this state of affairs is that employees in the former situation are likely to feel happier at work than those in the latter.…”
Section: Social Identity As a Byproduct Of Communicationmentioning
confidence: 99%
“…In particular, studies show that due to resource constraint, only a select number of leader-follower dyads are characterised by high-quality exchanges, and that, when they occur, these promote mutual liking, trust, and respect and thus serve to enhance employee satisfaction and wellbeing (Loi, Chan & Lam, 2014;Loi, Mao & Ngo, 2009). Indeed, this logic might apply to confidential information which is by definition not widely shared and exclusive.…”
Section: H3: That When Participants Receive Confidential Rather Than mentioning
confidence: 99%